The Controversy of Wujūdīyah Sufism: Muḥammad Zain ibn Faqīh Jalāl al-Dīn's Response to the Doctrine of the Seven Stages in the 18th Century - Masudi, Idris; Saepudin, Didin (Ulumuna, 2024)
This article discusses the teaching of the seven stages (martabat tujuh) in the 18th century, which had previously developed and became controversial in the Nusantara region since the 17th century. The seven stages are a central topic in philosophical Sufi teachings. The article's primary focus is the response of Muḥammad Zain ibn Faqīh Jalāluddīn al-Āsyī (d. 1783 CE), as articulated in his translation and commentary on the book Umm al-Barāhīn. Although the book he translated and commented on pertains to creed (aqīdah), he interjected his views regarding the seven stages. Using the socio-intellectual and historical approach, this study illustrates how Muḥammad Zain established the Sunni-Ash'ārī creed. The doctrine of the seven stages is complex, and finding competent scholars to explain it is challenging. However, Muḥammad Zain cautiously evaluates the proponents of the doctrine of the unity of existence, which forms the basis of the seven stages, such as Ibn Arabī and ‘Abd Karīm al-Jīlī. He even sharply criticizes those who mislead figures like Ibrāhim al-Kurānī, Aḥmad al-Qushāshī, and ‘Abdurraūf al-Fansūrī. Muḥammad Zain's views also reflect the dominance of the Sunni-Ash'ari creed, indirectly impacting the decline of philosophical Sufi trends in Aceh, particularly and in the Malay territory generally.